Juridical Review Of The People's Representative Council In Making Public Policies Through The Perspective Of Law Number 17 Of 2014 - Rinduwan Rinduwan; Lamijan Lamijan (CV. Publikasi Indonesia, 2023)
Legislation is one of the legal products of the number of existing legal products. The legislation contains general and abstract legal norms. It is general because existing legal norms apply to every legal subject in general. While being called abstract lies like legal norms which are not concrete in regulating legal events and are the object of regulation. Thus, a good law which incidentally is a type of legislation must have a philosophical basis, a sociological basis, and a juridical basis. Based on the principle of a rule of law, namely that government is organized based on laws, then in running a government it must refer to statutory regulations which become guidelines for the administration of a country based on the will of the people. The constitution is the guideline in the state and then elaborated in laws and regulations. This type of research is normative research. The approach used is a statutory approach (statute approach) and a conceptual approach (conceptual approach). The source of data used is secondary data. Data analysis was carried out in a qualitative descriptive manner. The conclusion is carried out using the deductive method, namely from general to specific, especially those related to the research topic, namely the Juridical Review of the House of Representatives in Making Public Policy in the Perspective of Law No. 17 of 2014. The result found community is concerned that in implementing or enforcing the law, justice is considered. In upholding the law, there must be a compromise between legal certainty, benefit, and justice, the three elements must receive proportional and balanced attention. Thus, legislation is a political product from which legislators turn into legal products when their preparation meets the elements of legal certainty, benefit, and justice in a proportional and balanced manner. There is a paradigm that the law governing representative institutions is part of a package of laws in the political field that needs to be changed. Laws governing representative institutions need to be seen as laws in the institutional context of the constitutional system. As previously stated, one of the problems that arise as a result of this law being considered as part of a package of regulations in the political field is institutional arrangements.